ANALISIS KONSEP KEPATUHAN BERAGAMA DARIPADA PERSPEKTIF ISLAM: AN ANALYSIS OF THE CONCEPT OF RELIGIOSITY FROM ISLAMIC PERSPECTIVE - Abdul Azis, Azra Qistina; Muwazir, Mohd Rizal (Online Journal of Islamic Management and Finance (OJIMF), 2021)
Religiosity is one of the variables that can influence one’s attitudes and behaviour in management decision making. This importance has led to various instruments being constructed around the world to measure them. However, it turns out that to date, only few instruments has been created for measuring religiosity from Islamic perspective. Religious beliefs and cultures differences is said to be one of the reasons why some of the scales being excluded particularly if they focus on Christianity. Meanwhile, there are few scholars argue that the elimination of “gender-specific’ item (for instance, El-Menouar model, 2014) is considered appropriate in measuring religiosity from Islamic perspective. However, the modified instrument is seen does not take into account the practice of sunnah in Islam. In contrast to the El-Menouar model which consist of: “basic religiosity”, “central duties”, “religious experience”, “religious knowledge” dan “orthopraxy”, this study adopts more comprehensive terms based on Shariah Islamiyah where the Quran and Hadith used as the primary foundation. Thus, “al-taqarrub”, “al-ibadah”, “al-ma’rifah”, “al-muraqabah” and “al-halal” dimensions are introduced as the concept of religiosity from Islamic perspective.